Adaptation and psychometric analysis of the Czech version of the Nurse Competence Scale - Pěrůžková Radana; Zeleníková Renáta; Gurková Elena; Kajander-Unkuri Satu; Štureková Lenka; Jarošová Darja (the Faculty of Health and Social Sciences of the University of South Bohemia in Ceske Budejovice in the Czech Republic, 2022)
Aim: The aim of the study was a transcultural adaptation, linguistic validation, and testing of psychometric properties of the Czech version of the Nurse Competence Scale (CZNCS).
Methods: Designed as a cross-sectional observational study. The sample comprised 274 students from third-year bachelor's nursing study programmes at Czech universities. To collect the data, a Czech version of the Nurse Competence Scale was used, containing 73 items grouped into seven subscales. The data was collected between 2018 and 2021. The internal consistency of the scale was assessed using Cronbach's alpha. Content validity was assessed using the Content validity index, while construct validity was tested using Principal Component Analysis. Differences in the assessment of competence were tested using the Mann-Whitney test and Pearson's chi-squared test.
Results: The content validity index average for the Czech version of NCS was 0.95, while the content validity index-universal agreement was 0.75. Cronbach's alpha of the Nurse Competence Scale was 0.981. Factor analysis showed a six-factor solution.
Conclusions: The Czech version of the Nurse Competence Scale showed good levels of content validity and reliability. The Czech version of the NCS may serve as a useful tool for self-assessment of students' competence in the final years of nursing programs.